2020
DOI: 10.6018/analesps.337011
|View full text |Cite
|
Sign up to set email alerts
|

Student profile not involved in bullying: description based on gender stereotypes, parenting practices, cognitive-social strategies and food over-intake

Abstract: El objetivo de la investigación es identificar las características del alumnado que no participa en episodios de bullying en función de estereotipos de género, crianza; actitudes  y estrategias cognitivas sociales y sobre-ingesta alimentaria. En el estudio participaron 1190 alumnos de educación básica de  once escuelas públicas del Estado de México, México. Investigación cuantitativa, con estudio descriptivo y diseño transversal. Se recogieron  datos a partir de cinco instrumentos que miden las variables de es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
0
1
0
1
Order By: Relevance
“…These stereotypes are assimilated from an early age. Therefore, it would be logical for intervention strategies against bullying to be directed at challenging and dismantling these deeply rooted sexist stereotypes in society [44].…”
Section: Discussionmentioning
confidence: 99%
“…These stereotypes are assimilated from an early age. Therefore, it would be logical for intervention strategies against bullying to be directed at challenging and dismantling these deeply rooted sexist stereotypes in society [44].…”
Section: Discussionmentioning
confidence: 99%
“…In studies examining specific bully-roles, traditional victims and not cyber-victims might have slightly higher levels of affective empathy, whereas only cyber-victims might have slightly higher levels of cognitive empathy when compared to outsiders or non-involved peers (Arató et al, 2020;Martínez et al, 2020). A third study, however, found that victims, compared to non-involved peers, had lower self-reported empathy (Mendoza-González et al, 2020). Some studies (9 out of 44), not comparing bullying roles, found that victimization related to less affective empathy (Chan & Wong, 2015), less cognitive empathy (Nasaescu et al, 2018;Williford et al, 2016) and less general empathy (Farrell et al, 2018;Jenkins et al, 2016Jenkins et al, , 2017Malti et al, 2010;Pistella et al, 2020;Yudes et al, 2020).…”
Section: Empathymentioning
confidence: 94%
“…Los resultados del estudio, complementan lo identificado en otras investigaciones (Mendoza et al, 2020), en las que señalan que "se deben dirigir esfuerzos para que, en escuelas y familias, principales micro sistemas de la sociedad, sean los que transmitan una educación a niños, niñas y jóvenes en la que incluyan comportamientos y actitudes, (...) que ayudarán a responder de forma integral a las exigencias de la sociedad actual". (p. 489) La implementación de programas de prevención del bullying es esencial para crear un entorno escolar seguro, promover valores de empatía y respeto, mejorar el rendimiento académico, prevenir problemas de conducta y proteger el bienestar de los estudiantes.…”
Section: Conclusionesunclassified